Transnational migration and Asia : the question of return - Baas, Michiel (Global Asia (Amsterdam, Netherlands), 2015)
As our increasingly globalized world alters the dynamics of migration, the ideas that migrants have about returning to their home countries have evolved as well. This diverse collection examines the changes and complexities of migration patterns in a range ofAsian countries and cities, exploring how globalization and transnationalism shape and give meaning to the migrant experience. From Japanese-Brazilian transmigrants and Filipina students in Ireland to skilled migrants from India, the authors address migrants'backgrounds, ambitions, and opportunities to offer intriguing insights and propose fascinating new questions about the lives of migrants in today's world